2013
DOI: 10.1155/2013/896749
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Japanese Encephalitis among Acute Encephalitis Syndrome Cases in West Bengal, India

Abstract: Background and Objectives. Japanese encephalitis (JE) is the most important cause of acute and epidemic viral encephalitis. Every year sporadic JE cases are reported from the various districts of West Bengal, indicating its endemicity in this state. JE vaccination programme has been undertaken by the State Health Department of West Bengal. This study was aimed at seeing the present scenario of JE among acute encephalitis syndrome (AES) cases in West Bengal. Materials and Methods. Blood and/or CSF samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 29 publications
7
38
0
Order By: Relevance
“…[8,9] The present study did not find any statistically significant sex predilection among AES and JE cases in accordance with other studies by Mohan et al [8] and Bandyopadhyay et al [9] Although, almost half hospitalisation occurred from people living in hilly area, but maximum JE cases was observed in persons living in plains. This might be mosquito habitat and chain of JE virus.…”
Section: Discussionsupporting
confidence: 91%
“…[8,9] The present study did not find any statistically significant sex predilection among AES and JE cases in accordance with other studies by Mohan et al [8] and Bandyopadhyay et al [9] Although, almost half hospitalisation occurred from people living in hilly area, but maximum JE cases was observed in persons living in plains. This might be mosquito habitat and chain of JE virus.…”
Section: Discussionsupporting
confidence: 91%
“…4 In a western study the incidence of AES was found to be 10.5-13.8/100000 populations. 5 In a study from Kolkata by Bhaswati Bhattacharya et al the incidence of JE was found 12.21%. 6 In a cohort study by Tom Soloman et al WHO JE surveillance standard study focus was on JE Positive or Negative or AES unknown mortality was 18.68% in JE positive cases which is almost similar to this study.…”
Section: Discussionmentioning
confidence: 96%
“…In the detec on of JEV, only 2 (2.2%) samples were tested posi ve, which is in contrast to other studies like Bandopadhya et al in 2011 (22.7%) and 2012 (5%) [24] and Dwivedi et al in 2012 (13.8%) [23].…”
Section: Discussionmentioning
confidence: 57%